Chronic unrelenting cough secondary to pericardial cyst impingement of right phrenic nerve. Issue 5 (24th May 2022) - Mikhail, John; Kennedy, Gregory; Singhal, Sunil; Resta, Isabella Tondi; Nadeem, Bilal; Azari, Feredun
Abstract: Located in the mediastinum, pericardial cysts are rare and benign congenital abnormalities commonly identified as incidental findings on imaging. However, some patients with abnormally enlarged cysts present with compressive symptoms, which include recurrent infections, tamponade from cardiac compression and respiratory complications. Our report highlights a challenging case of a patient with recurrent respiratory symptoms secondary to phrenic nerve compression. Misdiagnosis over the past decade resulted in ineffective interventions. After clear identification of the cyst compression of the ipsilateral phrenic nerve, the patient underwent a minimally invasive robotically assisted cyst resection with phrenic nerve preservation that alleviated respiratory symptoms.